2014
DOI: 10.4141/cjas-2014-033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of calving seasons and feeding systems in western Canada. I. Postweaning growth performance and carcass characteristics of crossbred steers

Abstract: Durunna, O. N., Block, H. C., Iwaasa, A. D., Thompson, L. C., Scott, S. L., Robins, C., Khakbazan, M. and Lardner, H. A. 2014. Impact of calving seasons and feeding systems in western Canada. I. Postweaning growth performance and carcass characteristics of crossbred steers. Can. J. Anim. Sci. 94: 571–582. Crossbred steers (n=272) weaned from early (EC) and late (LC) calving systems (CS) were used to evaluate the impact of two feeding systems (FS) on postweaning performance and carcass characteristics. The stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…The clusters defined in our study were characterised both by calving season and feeding management, for example, the duration of pasture. This result is consistent with that of Durunna et al (2014) who observed a significant interaction between the calving season and the nature of the diet, which did not lead to a clear conclusion about the effect of the calving season alone.…”
Section: Suckling Periodsupporting
confidence: 90%
“…The clusters defined in our study were characterised both by calving season and feeding management, for example, the duration of pasture. This result is consistent with that of Durunna et al (2014) who observed a significant interaction between the calving season and the nature of the diet, which did not lead to a clear conclusion about the effect of the calving season alone.…”
Section: Suckling Periodsupporting
confidence: 90%
“…However, when evaluated by trained sensory panelists, there were no differences reported for flavor, tenderness, juiciness, or overall satisfaction (Moody et al, 1970). Other researchers have evaluated marbling texture; however, comparisons were not made among the marbling texture groups in most of these studies (Goll et al, 1965;Cross et al, 1975;Cross, 1977;Dubeski et al, 1997;de Mello et al, 2012ade Mello et al, , 2012bDurunna et al, 2014). Therefore, the objective of the current study was to evaluate the effects of marbling texture on consumer and trained sensory panel ratings of beef strip loins varying in marbling texture (fine, medium, and coarse) from 3 USDA quality groups.…”
Section: Introductionmentioning
confidence: 97%
“…www.meatandmusclebiology.com both levels (Smith et al, 2001). Marbling texture is impacted by a variety of factors including breed Yang et al, 2006;Albrecht et al, 2011) and animal diet (Dubeski et al, 1997;de Mello et al, 2012a, b;Durunna et al, 2014). But marbling texture's impact on beef palatability is unclear as it has not been the primary focus of much previous work.…”
Section: Marbling Texturementioning
confidence: 99%
“…However, summer calving has the potential to match the cows' nutrition with available forage, thereby reducing the cost of production. A companion study (Durunna et al 2014a) evaluated the impact of these two calving systems (CS) and two feeding systems (CS) on growing steers in western Canada. The results demonstrated that production decisions that producers make during breeding have consequences on subsequent postweaning growth performances of steers and profitability (Durunna et al 2014a, b;Khakbazan et al 2014).…”
mentioning
confidence: 99%